Interactions between plants and soil shaping the root microbiome under abiotic stress - Hartman, Kyle; Tringe, Susannah G (Biochemical journal, 2019)
Plants growing in soil develop close associations with soil microorganisms, which inhabit the areas around, on, and inside their roots. These microbial communities and their associated genes - collectively termed the root microbiome - are diverse and have been shown to play an important role in conferring abiotic stress tolerance to their plant hosts. In light of growing concerns over the threat of water and nutrient stress facing terrestrial ecosystems, especially those used for agricultural production, increased emphasis has been placed on understanding how abiotic stress conditions influence the composition and functioning of the root microbiome and the ultimate consequences for plant health. However, the composition of the root microbiome under abiotic stress conditions will not only reflect shifts in the greater bulk soil microbial community from which plants recruit their root microbiome but also plant responses to abiotic stress, which include changes in root exudate profiles and morphology. Exploring the relative contributions of these direct and plant-mediated effects on the root microbiome has been the focus of many studies in recent years. Here, we review the impacts of abiotic stress affecting terrestrial ecosystems, specifically flooding, drought, and changes in nitrogen and phosphorus availability, on bulk soil microbial communities and plants that interact to ultimately shape the root microbiome. We conclude with a perspective outlining possible directions for future research needed to advance our understanding of the complex molecular and biochemical interactions between soil, plants, and microbes that ultimately determine the composition of the root microbiome under abiotic stress.